Compulsory drug detention and injection drug use cessation and relapse in Bangkok, Thailand. (10th October 2014) - Fairbairn, Nadia; Hayashi, Kanna; Ti, Lianping; Kaplan, Karyn; Suwannawong, Paisan; Wood, Evan; Kerr, Thomas
Abstract Introduction and Aims Strategies to promote the reduction and cessation of injection drug use are central to human immunodeficiency virus prevention and treatment efforts globally. Though drug use cessation is a major focus of drug policy in Thailand, little is known about factors associated with injection cessation and relapse in this setting. Design and Methods A cross‐sectional study was conducted between July and October 2011 of a community‐recruited sample of people who inject drugs in Bangkok, Thailand. Using multivariate logistic regression, we examined the prevalence and correlates of injection drug use cessation with subsequent relapse. Results Among 422 participants, 209 (49.5%) reported a period of injection drug use cessation of at least one year. In multivariate analyses, incarceration (adjusted odds ratio [AOR] 13.07), voluntary drug treatment (AOR 2.75), midazolam injection (AOR 2.48) and number of years since first injection (AOR 1.07) were positively associated with injection cessation of duration greater than a year (all P < 0.05). Exposure to compulsory drug detention was positively associated (AOR 2.61) and methadone treatment was negatively associated (AOR 0.38) with short‐term cessation only. Injection drug use cessation was most often due to incarceration (74%), and relapse was associated with release from prison (66%). Discussion and Conclusion Half of the study participants had previously stopped injecting drugs for more than a year, and this was strongly associated with incarceration. Compulsory drug detention was associated with short‐term cessation and relapse. A range of evidence‐based strategies should be made available to facilitate sustained cessation of injection drug use in Thailand. [Fairbairn N, Hayashi K, Ti L, Kaplan K, Suwannawong P, Wood E, Kerr T. Compulsory drug detention and injection drug use cessation and relapse in Bangkok, Thailand. Drug Alcohol Rev 2015;34:74–81]